Filamin-A is required for the incorporation of tissue factor into cell-derived microvesicles - Collier, Mary E. W.; Maraveyas, Anthony; Ettelaie, Camille (Thrombosis and Haemostasis, 2014)
We previously reported that the incorporation of tissue factor (TF) into cell-derived microvesicles (MVs) is regulated by the phosphorylation of the cytoplasmic domain of TF. Since the cytoskeletal protein filamin-A is known to bind to the cytoplasmic domain of TF in a phosphorylation-dependent manner, the involvement of filamin-A in the incorporation of TF into MVs was examined. Endothelial cells were transfected to express TF, whereas MDA-MB-231 cells were used to examine endogenously expressed TF. MV release was induced by activating protease-activated receptor-2 (PAR2). Partial suppression of filamin-A expression using two different filamin-A siRNA sequences resulted in significant reductions in the incorporation of TF antigen into MVs as determined by TF-ELISA and western blot analysis, and was reflected in reduced thrombin-generation and FXa-generation capacities of these MVs. Deletion of the cytoplasmic domain of TF also resulted in reduced incorporation of TF into MVs, whereas the suppression of filamin-A expression had no additional effect on the incorporation of truncated TF into MVs. Partial suppression of filamin-A expression had no effect on the number and size distribution of the released MVs. However, >90% suppression of filamin-A expression resulted in increased MV release, possibly as a result of increased instability of the plasma membrane and underlying cytoskeleton. In conclusion, the presence of filamin-A appears to be essential for the incorporation of TF into MVs following PAR2 activation, but is not required for the process of MV formation and release following PAR2 activation.
Keywords: Tissue factor; filamin-A; microvesicles; microparticles; endothelial cells